2016
DOI: 10.1128/genomea.01426-16
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of the Industrial Bacterium Ketogulonicigenium vulgare SKV

Abstract: Ketogulonicigenium vulgare has been widely used in vitamin C two-step fermentation, which converts l-sorbose to 2-keto-l-gluonic acid. Here, the complete genome of K. vulgare SKV, which performs better fermentation production than K. vulgare Hbe602, is deciphered to understand the key differences in metabolism between K. vulgare strains SKV and Hbe602.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The same recent studies on L. sericata bacterial content 11 , 35 revealed Proteus as the most abundant genus detected, being identified from the digestive tract, salivary glands and the adult stage 48 , 49 . However, the study of Gasz et al 46 revealed the dominant presence of Pseudomonas and Corynebacterium in all L. sericata organs, while Proteus was observed in low abundances.…”
Section: Discussionsupporting
confidence: 61%
“…The same recent studies on L. sericata bacterial content 11 , 35 revealed Proteus as the most abundant genus detected, being identified from the digestive tract, salivary glands and the adult stage 48 , 49 . However, the study of Gasz et al 46 revealed the dominant presence of Pseudomonas and Corynebacterium in all L. sericata organs, while Proteus was observed in low abundances.…”
Section: Discussionsupporting
confidence: 61%
“…vulgare strains (including K. vulgare SKV, SPU B805, Y25, Hbe602, and WSH-001) revealed that the strains SKV and SPU B805 lack 6-phosphofructokinase (EC 2.7.1.11, Pfk) of the EMP pathway, as well as the key enzymes 2-keto-3-deoxy-6-phosphogluconate aldolase (EC 4.1.2.14, Eda) and 6-phosphogluconate dehydratase (EC 4.2.1.12, Edd) of the ED pathway. The EMP and ED pathways are therefore incomplete in these strains, and carbohydrate metabolism in the strains SKV and SPU B805 has been speculated to chiefly occur through the PPP pathway .…”
Section: Characteristics Of Key Strains Employed In the Classic Two-s...mentioning
confidence: 99%
“…However, Ur Ba Nce et al [21] classified these bacteria as Ketogulonigenium vulgare after phenotype and genotype analysis in 2001. So far, whole-genome sequencing has been completed for K. vulgare Y25 [30], WSH-001 [31], Hbe602 [32], SKV [33], and SPU B805 [34].…”
Section: Metabolic Defects Of K Vulgare and The Effects Of Different ...mentioning
confidence: 99%